"A scarlet letter": Stigma and other factors affecting trust in the health care system for women seeking substance abuse treatment in a community setting. Issue 2 (3rd April 2019) - Cockroft, Joshua D.; Adams, Susie M.; Bonnet, Kemberlee; Matlock, Deondria; McMillan, Jessica; Schlundt, David
Abstract: Background: Trust in health care has been shown to influence health care utilization, perceptions of fair treatment, and health outcomes in the general population. The literature on trust in health care in individuals with a history of substance use disorder (SUD) is more limited, primarily examining the patient-provider relationship. Women seeking substance abuse treatment in community-based programs have higher rates of prior trauma and health disparities compared with male counterparts and the general population. With higher rates of prior trauma, this population is theoretically at high risk of decreased interpersonal trust and altered interpersonal relationships. Objective: This study sought to identify factors influencing trust in the health care system for women seeking substance abuse treatment in a community-based residential treatment program. Methods: Six client focus groups ( n  = 30), 1 provider focus group ( n  = 7), and 2 individual clinical administrator interviews ( n  = 2) were conducted between November 2016 and August 2017. Focus groups and interviews were audio recorded and transcribed. Coding and coding reconciliation were conducted by 2 independent coders. Themes were extracted and analyzed from sorted and coded quotes. Results: Six themes emerged. Factors that influence trust in the health care system in this population include (1) prior experiences with diagnosis, treatment, and outcomes; (2) stigma of addiction; (3) payment and reimbursement structure; (4) patient rights and protections; (5) efficiency-driven care; and (6) the health care system's role in causing and/or enabling addiction. Conclusions: These themes demonstrate a general distrust of the health care system by women in this population. Distrust is influenced by a perception of a health care system providing care that is variable in quality, often stigmatizing, unaffordable, efficiency driven, and often influencing individuals' SUD. This aligns with and extends prior literature around trust of health care in individuals with SUD. Future directions in research include formally assessing the impact of trust on health outcomes such as treatment entry and retention.